2021
DOI: 10.3390/app11094043
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Research on Reinforced Concrete Columns Strengthened with Steel Jacket and Concrete Infill

Abstract: Experimental research on axially compressed columns made from reinforced concrete (RC) and RC columns strengthened with a steel jacket and additional fill concrete is presented in this paper. A premade squared cross-section RC column was placed inside a steel tube, and then the space between the column and the tube was filled with additional concrete. A total of fourteen stub axially compressed columns, including nine strengthened specimens and five plain reinforced concrete specimens, were experimentally test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 34 publications
(62 reference statements)
0
4
0
Order By: Relevance
“…Generally, the TCCFST column's load-bearing capacity increases with a higher compressive strength of the infill concrete. It was shown that, when the confinement factor increases, the influence of the concrete strength on the coefficient of the enhanced strength, ks, decreases [1].…”
Section: Comparative Analysis Of the Test Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Generally, the TCCFST column's load-bearing capacity increases with a higher compressive strength of the infill concrete. It was shown that, when the confinement factor increases, the influence of the concrete strength on the coefficient of the enhanced strength, ks, decreases [1].…”
Section: Comparative Analysis Of the Test Resultsmentioning
confidence: 99%
“…Generally, the TCCFST column's load-bearing capacity increases with a higher compressive strength of the infill concrete. It was shown that, when the confinement factor increases, the influence of the concrete strength on the coefficient of the enhanced strength, ks, decreases [1]. After the concluded experiments, the steel tube was partially removed from one chord of the TCCFST column to investigate the mode of failure and to note the cracking and/or crushing of the concrete fill.…”
Section: Comparative Analysis Of the Test Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Landović and Bešević [8] investigated the axial capacity of composite columns made of square RC columns strengthened with steel tubes and filled with concrete. The use of welded composite columns for retrofitting frames proved to be very successful since it increased the ultimate capacity, effective stiffness and energy dissipation [8].…”
Section: Introductionmentioning
confidence: 99%